1972
DOI: 10.1084/jem.136.3.532
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immunity and Tolerance in Vitro by Hapten Protein Conjugates

Abstract: A critical stage in the induction of antibody responses is the interaction of antigen molecules with the surface receptors of immunocompetent cells. This interaction may result in either immunity, or its opposite, immune tolerance. The differences between the pattern of antigen binding to nonthymus-dependent lymphocytes (B cells) 1 in immunity and tolerance are not fully understood. Recently, attempts were made to study this problem in tissue culture, using dinitrophenylated polymeric flagellin (DNP POL) as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The evidence presented in this study also confirms previous reports that demonstrated that soluble antigens may bind to mature B cells and even inhibit stimulation, but, if the antigen is removed before stimulation, the B cells remain unaffected (45,46). Therefore, it appears that the "one signal" mode (antigen binding to B cells) is irrelevant to mature B cells but tolerogenic to developing B cells (Table IV).…”
Section: Antigen Concentration and Carrier Independence Of Tolerance supporting
confidence: 79%
“…The evidence presented in this study also confirms previous reports that demonstrated that soluble antigens may bind to mature B cells and even inhibit stimulation, but, if the antigen is removed before stimulation, the B cells remain unaffected (45,46). Therefore, it appears that the "one signal" mode (antigen binding to B cells) is irrelevant to mature B cells but tolerogenic to developing B cells (Table IV).…”
Section: Antigen Concentration and Carrier Independence Of Tolerance supporting
confidence: 79%
“…In the present context, its main usefulness was to yield higher plaque numbers in control cultures of spleen cells from nude mice, and it is of interest that the nonresponsiveness caused by DNP-D-GL could be maintained despite the addition of this adjuvant-like material. Table I also shows that concentrations of DNP-D-GL of 10 ng/ml and above gave significant impairment of DNP- (8). However, this would require that DNP-I)-GL remain at the lymphocyte surface and not be removed by "capping" and receptor pinocytosis (13, 14), since DNP-FLA was present continuously during the 3 day challenge period.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, each molecule carries many DNP residues, so one could envisage efficient receptor cross-linking with DNP-D-GL. Yet highly DNP-substituted albumins and globulins are not good tolerogens in vitro (2,8). A careful stud)-of tolerogenicity with hapten substitution rate as the key variable would be revealing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further suggested by the results of Greaves and Baumingcr (1972), who found that phytohacipaggiutiiiin and pokeweed mitogen coupled to Sepharose beads stimulated T and B cells, although the mitogens could not be taken into the cell. The degree of binding and extent of cross-linking between receptors may provide the method of signal discrimination between immunity and tolerance, as suggested by Feldmann (1972). Binding of the Ag to its receptor may then cause a conformational change which results in the activation of a membrane-associated enzyme, such as aden)l cyclase, to produce a "second messenger" carrying the signal to the nucleus.…”
Section: Disgussionmentioning
confidence: 99%